On-line Spectrophotometric Method for Decolourizing Reaction Kinetics of Reactive Black 5 by Fenton Oxidation - Xu, Hang; Li, Guozhi (Asian Journal of Chemistry, 2013)
Fenton oxidation was employed to treat and decolourize the modeling wastewater of reactive black 5 by online spectrophotometry. The effects of initial FeSO4 dosage, initial H2O2 dosage, pH value, initial reactive black 5 and temperature on the colour removal and decolourizing reaction rate constant were investigated. The results show that Fenton oxidation follows pseudo first order kinetics in the first stage and reaction activation energy is 3.451 kJ mol-1. The optimum initial H2O2 and pH was 2.118 mM and 3, respectively. Initial FeSO4 dosage against kap presents a linear correlation: kap = 0.1354 [Fe2+]o. Intrinsic reaction rate constant of reactive black 5 and ˇOH is 7.528 × 1011 M-1 s-1.